Dweet Mottle Disease Probably is Caused by Citrus Leaf Blotch Virus - Vives, María C.; Pina, José A.; Juárez, José; Navarro, Luis; Moreno, Pedro; Guerri, José (IOCV, 2021)
Dweet mottle disease was first detected in Cleopatra mandarin CRC-270 in California and causes chlorotic blotching in Dweet tangor seedlings. Nagami kumquat SRA-153 induces similar symptoms in this indicator, but additionally causes vein clearing in several citrus species, stem pitting in Etrog citron, and bud-union crease when propagated on Troyer citrange. Citrus leaf blotch virus (CLBV) was found in this kumquat and its genomic RNA sequenced, thus allowing its detection by molecular hybridization and RT-PCR assays. Two Californian sources of Dweet mottle (DMV-931 and DMV-932) and kumquat SRA-153 were graft-inoculated on Pineapple sweet orange, Dweet tangor, Etrog citron and Nules Clementine and infected Clementine buds were then propagated on Carrizo citrange rootstock. Kumquat SRA-153 induced bud-union crease of Nules Clementine on citrange, vein clearing in Pineapple sweet orange, chlorotic blotching in Dweet tangor and stem pitting in Etrog citron, whereas Dweet mottle sources only induced blotching in Dweet tangor and stem pitting in Etrog citron. Fragments of the CLBV genome were RT-PCR amplified from indicator plants inoculated with either kumquat SRA-153 or Dweet mottle sources. The nucleotide identity between CLBV isolate SRA-153 and the DMV-931 and DMV- 932 sources was 96.6% and 96.8% in a region of the RNA replicase gene, and 98.7% and 98.5% in the coat protein gene, respectively. These data and previous findings that Dweet mottle and CLBV are difficult to eliminate by shoot-tip grafting or thermotherapy, suggest that Dweet mottle may be caused by CLBV, and that, besides CLBV, a different pathogen causing bud-union crease and vein clearing may be present in kumquat SRA-153 but not in DMV-931 and DMV-932 sources.